On the problem of novel composite materials development for car brake rotor - Fu, P.; Gorin, A.; Debnath, Sujan; Oo, Z. (World Academy of Science, Engineering and Technology (WASET), 2012)
This paper presents a study of the potential materials that are suitable for the development of the automotive brake disc. Two new materials are proposed as an alternative material to the conventionally used gray cast iron for the disc brake, which are namely Metal Matrix Composite (MMC) and Functionally Graded Material (FGM). MMCs with ceramic particulate reinforcement are found to have a low density and high thermal conductivity compared to the cast irons. Two particulate reinforcements, Al2O3 and SiC were being considered for MMC. On the other hand, FGM has demonstrated high thermal shock resistance, better wear resistance and low density. Preliminary investigation indicated that MMC acquired improved hardness property. Meanwhile, the hardness property of FGM with Al2O3 and Al2TiO5 as layered composites materials can be further improved.